Mine Action in Ukraine as an Administrative and Legal Category - V. I. Teremetskyi; M. Yu. Marchenko (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The scientific article is devoted to the issue of defining mine action in Ukraine as an administrative and legal category, identifying existing gaps in legislative regulation, and outlining directions for their elimination. The legislative understanding of the term “mine action” and its component elements is clarified. It is noted that the key element of mine action is demining. The article emphasizes that the Law of Ukraine “On Mine Action” covers only humanitarian demining, which limits the concept of “mine action” to peacetime needs. This contradicts the international IMAS standards, which distinguish other types of demining as well.